THE EFFECT OF BANKING HEALTH LEVEL ON SUSTAINABILITY DISCLOSURE IN THE BANKING SECTOR - Maulana Irsyad; Khalilul Rahman; Sanda Patrisia Komalasari (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2025)
This study examines the effect of bank health on sustainability disclosure in Indonesia’s banking sector. Using a quantitative, causal approach, the research analyzes data from 123 observations of banks listed with the Indonesian Financial Services Authority between 2021 and 2023, selected through purposive sampling. The results indicate that bank health does not significantly influence sustainability disclosure, suggesting that higher levels of financial health do not necessarily lead to greater transparency in sustainability reporting. This finding highlights that banks with strong financial performance may prioritize profitability over sustainability issues. The study underscores the importance of balancing financial stability and sustainability disclosure, recommending that banks and policymakers develop strategies to encourage both. These results also suggest the need for further research to explore other factors—such as regulatory frameworks, market dynamics, or organizational culture—that may affect the relationship between bank health and sustainability disclosure. By addressing these aspects, the banking sector can better contribute to sustainable development goals.